INFANT MORTALITY AND FAMILY HEALTH STRATEGY IN THE 3RD HEALTH REGIONAL OF PARANÁ, FROM 2005 TO 2016 - Geovani Allan Broday; Ana Cláudia Garabeli Cavalli Kluthcovsky (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: To analyze the temporal trend in infant mortality and in populational coverage by the Family Health Strategy and associated factors with infant mortality in the municipalities of the 3rd Health Regional of Paraná, Southern Brazil. Methods: Ecological time series study, with data from the Mortality Information System (Sistema de Informação Sobre Mortalidade - SIM), the Live Birth Information System (Sistema de Informação Sobre Nascidos Vivos - SINASC) and the Support Room for Strategic Management (Sala de Apoio à Gestão Estratégica - SAGE), from 2005 to 2016. Trends were calculated using polynomial regression. The associated factors with infant mortality were maternal, perinatal and obstetric variables. The significance level adopted was 5%. Results: Between 2005 and 2016, there were 115,796 births and 1,575 deaths of children under 1 year of age. Considering the municipalities together, the populational coverage by the Family Health Strategy went from 43.8% in 2005 to 66.4% in 2016 and the infant mortality from 17.1/1,000 live births in 2005 to 10.7/1,000 live births in 2016. The trend over time of populational coverage by the Family Health Strategy was crescent and of infant mortality was decrescent, for most municipalities. The factors associated with greater chances of death in children under 1 year of age were preterm gestational age (Odds Ratio - OR=15.05; 95% confidence interval - 95CI% 13.54-16.72), low birth weight (OR=15.14; 95%CI 13.61-16.84), multiple gestation (OR=4.51; 95%CI 3.74-5.45) and mother with up to 7 years of study (OR=1.93; 95%CI 1.74-2.14). Conclusions: Crescent trend in coverage by the Family Health Strategy was accompanied by a decrescent trend in infant mortality. The results can be a source of information for the strengthening of mother-child health actions, considering local and regional specificities.